Incidence and evolution of venous thrombosis during the first 3 months after irreversible electroporation of malignant hepatic tumours - W. Bäumler (Nature Portfolio, 2019)
Abstract The incidence and evolution of venous thrombosis adjacent to the ablation zone after percutaneous irreversible electroporation (IRE) were evaluated to identify potential risk factors in patients with hepatic malignancies. 205 venous structures (in 87 patients) within a ≤1.0 cm radius of the ablation zone were assessed after IRE of 112 hepatic lesions (74 primary, 38 secondary hepatic malignancies) by pre-interventional and post-interventional (1–3 days, 6 weeks and 3 months after IRE) contrast-enhanced magnetic resonance imaging. The relationships between venous thrombosis and clinical features were analysed using a binary logistic regression model. In 27 of 87 patients (31%), a total of 67 venous complications were noted during the 3 months follow-up. Thrombosis represented the most frequently observed complication (n = 47; 70.1%), followed by vessel narrowing (n = 20; 29.9%). 5 (10.6%) of 47 thromboses showed spontaneous regression 3 months after IRE. A small vessel diameter (p = 0.011) and post-interventional vessel narrowing (p = 0.006) were independently associated with delayed post-ablative thrombosis. Delayed venous thrombosis frequently occurs after IRE of hepatic malignancies. Pre-existing vessel narrowing and a small vessel diameter represent significant risk factors that require further surveillance and potentially therapeutic intervention.